Pendidikan Islam Dalam Perspektif Psikologi Lintas Agama dan Budaya - marno marno marno (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
Islamic education psychology is an important part of character configuration in the context of the totality of psychological and socio-cultural processes in interfaith and culture can be grouped in the heart (spiritual and emotional development), intellectual development, sports and kinesthetic (physical and kinetic development) ), and though feeling and intention (affective and creativity development).Psychology across religions and cultures is a scientific study of human behavior and its implications, which emerge and are influenced by social, religious and cultural forces that appear together and give rise to variants, behavior, experience and appreciation. In life in this world, plurality and multiculturalism is a necessity because it must be recognized by everyone. On the other hand, this is wealth for a nation that can encourage people to compete in achieving goodness. Keyword: Islamic education, religious and cultural psychology.